SAT0120 Ninja, A Japanese Rheumatoid Arthritis Database, Demonstrated that the Size and Number of Swollen Joints Correlated with Increased Systemic Inflammation Markers. Digital Joint Swelling Showed Only Trace Increases of Serum C-Reactive Protein and Erythrocyte Sedimentation Rate. (9th June 2015) - Shimada, K.; Komiya, A.; Onishi, K.; Kise, T.; Miyoshi, Y.; Nagai, Y.; Kikuchi, E.; Nunokawa, T.; Sawaki, T.; Yokogawa, N.; Sugii, S.; Tohma, S.
Abstract : Background: Polyarthritis caused by rheumatoid arthritis has wide variety in size and number of affected joints. In diagnosis and evaluation, swollen joint count and systemic inflammation markers ( e.g. serum C-reacive protein (CRP) and erythrocyte sedimentation rate (ESR)) are considered independently. However, when systemic inflammation markers are supposed to reflect the total inflammation in the whole body, the level of the markers should vary according to the size and the number of the swollen, that is, inflamed joints. Objectives: To investigate the correlation between the size of swollen joints with systemic inflammation markers using a large-scale patient database. Methods: NinJa is the largest database of rheumatoid arthritis in Japan in which more than 10, 000 patients are registered. Data registered to the NinJa database in 2012 were used. Sixty-six joints were classified into 3 size categories, namely, the digital joints (distal interphalangeal joints, proximal interphalangeal joints, interphalangeal joints, metacarpophalangeal joints and metatarsophalangeal joints) and acromioclavicular joints as small joints (joint surface area 1 <10 cm 2 ), the knees as large joints (joint surface area 1 >100 cm 2 ), and the others as medium-sized joints (joint surface area 1 between 10 cm 2 and 100 cm 2 ). Patients with swollen joints limited to one joint-size category were grouped by swollen joint count and compared with patients with no swollen joint. 8574 cases were analyzed. Patients receiving anti-interleukin-6 or Janus-kinase-inhibiting therapies were excluded. Results: Patients with larger numbers of swollen joints tended to show higher levels of both serum CRP and ESR in each joint-size category (Figure 1 ). In the medium-sized, or knee joint group, these levels were significantly higher than in the no-swelling group and small joint group with the same swollen joint count. Linear regression analysis revealed increments of CRP (mg/L) (ESR (mm/1hr) [95% confidence interval]) per swollen joint as 4.6 [3.7-5.5] (8.9 [6.5-11]) in the knee, 2.3 [2.0-2.7] (4.9 [4.0-5.9]) in medium-sized joints, and 0.56 [0.35-0.77] (0.89 [0.39-1.38]) in the small joints. Conclusions: The strength of swelling in the joints affecting systemic inflammation markers increased with the involvement of larger and/or more numerous joints. References: Am J Med Sci. 1956;232:150-5 Disclosure of Interest: None declared